The impact of Hashimoto’s thyroiditis on the diagnostic utility of P63 and CK19 immunohistochemistry markers in predicting thyroid cancer - Karunakaran, Poongkodi; Jayaraman, Sujatha; Periyasamy, Sumathi; Subburaman, Ramesh (International Surgery Journal, 2024)
Background: The incidence of thyroid cancer (TC) and Hashimoto’s thyroiditis (HT) is increasing worldwide. Coexisting HT adds to diagnostic confusion in establishing TC on histopathological examination (HPE). Studies have shown the promising role of immunohistochemistry markers in predicting cancer, but the impact of coexisting HT is unclear. This prospective study determined the impact of HT on the diagnostic utility of p63 and CK19 in predicting thyroid cancer. Methods: Out of 103 patients undergoing total thyroidectomy for benign or malignant thyroid nodules, 31 patients (mean age=39.7 years, Male:Female=4:27) with elevated thyroid autoantibodies were studied. HPE of formalin-fixed paraffin-embedded tissue from surgical specimens confirmed the final diagnosis. Sections 2-4μ were stained for immunohistochemistry using the standard avidin-biotin complex method with antibodies against P63 and CK19. Expression in 10% or more of neoplastic cells qualified as positive while expression in less than 10% was considered negative. Receiver Operating Characteristic (ROC) assessed the diagnostic accuracy. Results: Histopathology comprised 58.1% benign and 41.9% malignant lesions. CK19 exhibited membranous expression in 87.1%, while p63 exhibited focal nuclear expression in 35.5% of cases. In ROC analysis predicting TC for entire cohort, the area under curve (AUC) of P63 was 0.6 and CK19 was 0.532. In subgroup with HT, the AUC of p63 was 0.8. Each P>0.05. Conclusions: P63 expression had better predictability for thyroid cancer with co-existent Hashimoto’s thyroiditis but was not statistically significant. Whereas, CK19 was non-specific and unreliable. Histomorphological features on HPE are the gold standard for diagnostic decisions.